Contribution of T.M. Hasbi Ash-Shiddieqy in the Renewal of Islamic Law in Indonesia - Asy'ari Asy'ari (Budapest International Research and Critics University, 2022)
T.M. Hasbi ash-Shiddieqy is one of the leading reformers of Islamic law in Indonesia. He initiated the idea to draft Islamic law in accordance with the socio-culture of Indonesian society called